EVALUATION OF CAPABILITY OF CARBON FOOTPRINT REDUCTION FROM GRAIN MAIZECULTIVATION - Tomasz Żyłowski; Aleksandra Król; Jerzy Kozyra (Annals of the Polish Association of Agricultural and Agribusiness Economists)
The aim of the study is to assess the possibility of reducing greenhouse gas (GC) emissions in thecultivation of maize for grain using the method combining carbon footprint (CF) and Data EnvelopmentAnalysis (DEA). The analysis used survey data from 32 farms. The quantitative assessment of greenhousegas emissions with a breakdown into the main emission sources was presented, and then the possibilitiesof limiting the level of GHG emission in these farms were determined. The emission reduction potentialfor the analyzed farms was specified in the range from 94 to 1,047 kg CO2-eq/ha (from 3.3 to 33.4%).